General narratology and the three forms of existence of narrative in music. Marta Grabocz. Translated from French into Spanish by Alberto Leongómez H. - Marta Grabocz; Alberto Leongomez Herrera (Pensamiento Palabra y Obra, 2012)
La narratología general y los tres modos de existencia de la narrativa en música Marta Grabocz Traducción del Francés: Alberto Leongómez H.